El estrés postraumático en la vida de una joven universitaria y como afecta su entorno social - Oña Guerra, Erickson Jandari (2021)
The present case study was developed with a post-traumatic stress problem in a university adolescent from the Province of Manabí in the Canton Portoviejo. The symptoms reflected by the university adolescent are presented with a higher incidence in the psychic area due to the disturbing thoughts that affect her in her social environment. In the collection of information, techniques such as the semi-structured interview, medical history and the Hamilton test were used to obtain a presumptive diagnosis. In addition, techniques of the cognitive behavioral model were applied, through which they helped to detect the distorted thoughts of the patient to modify those thoughts, these being cognitive restructuring techniques.